Has COVID-19 Threatened Relational Identity? Risk Representation, Identity Threats, and Perceived Health during Quarantine. Issue 3 (3rd July 2022) - Mancini, Tiziana; Imperato, Chiara
ABSTRACT: Based on the Identity Process Theory, this study wondered whether COVID-19 risk representation threatened relational identity and health perception. A sample of 976 Italian university students ( Mage = 24.2; females: 73.8%) and a sample of 204 university staff members ( Mage = 50.86; females: 57.4%) completed an online survey during the 1 st phase of COVID-19. The results confirmed that in both samples the COVID-19 risk representation has been related to participants' identity, both activating identity protection strategies and threatening their relational identity, i.e., the identity they derived from family and friendship relationships. Furthermore, identity protection mediated the relation between risk representation and health perception, suggesting that to feel even more part of their family and friend groups can protect participants from feeling unhealthy.